Incentives of derivative hedging: Evidence from German non-financial corporations - Pfleiderer, Felix (2016)
This thesis empirically investigates the determinants of derivative hedging by German non-financial corporations. The sample consists of 397 corporations observed over a period of five-years, where a keyword approach is utilised to collect data on hedging activity from annual reports. Univariate and multivariate logit regressions show that derivative hedging is prominent in larger corporations and corporations facing foreign exposure. The analysis in this study further recognises the existence of a potential bias created by inclusion of natural-hedger and speculators in the sample. The findings of multivariate regressions excluding those groups show if any an only marginally weakening effect on the hypothesis that corporations hedge due to expected costs of financial distress, price exposure and liquidity. The hypothesis of underinvestment costs as a motivating factor to hedge with derivatives is only supported limited in the sample concerned. Beyond this, univariate tests on post-hedging measures of the only interest rate exposed sample suggest that derivatives are used significantly to enhance returns thus increasing a corporations’ value and furthermore implying speculation.